XYLOSE ISOMERASE SYNTHESIS IN ACTINOBACTERIA ARTHROBACTER UREAFACIENS BIM B-6 - Л. І. Сапунова (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2008)
The role of different carbon sources in biosynthesis of cell-bound xylose isomerase by Arthrobacter ureafaciens BIM B-6 was investigated. It was found that in this prokaryotic actinobacterium enzyme production is under control of induction and catabolite repression. High level of xylose isomerase production was recorded when bacterium was grown both on xylose media and on media with soy, citrus pulp and wheat bran.